2018
DOI: 10.16970/entoted.380010
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid resistance of Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) in cotton fields of Çukurova Region, Turkey

Abstract: Cotton aphid, Aphis gossypii Glover, 1877 (Hemiptera: Aphididae), is a major pest in cotton fields. Neonicotinoids are important and highly prevalent insecticides currently used against A. gossypii and other herbivorous insect pests in the Mediterranean Region of Turkey. However, some insecticide applications against A. gossypii in the Çukurova Region have failed despite using high rates. Therefore, bioassays and enzyme analyses were conducted to determine resistance to imidacloprid and thiamethoxam in A. goss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
(46 reference statements)
4
13
0
Order By: Relevance
“…The weakest GST activity was found in the Akyuva population (1.05 U/ml) (Table 1). Likewise, it was reported that, 3.3 times more enzyme activity was found in the neonicotinoid-resistant A. gossypii populations in the province of Adana in 2016 (Ulusoy et al 2018). These results provide evidence that these populations have metabolic resistance still in this region.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The weakest GST activity was found in the Akyuva population (1.05 U/ml) (Table 1). Likewise, it was reported that, 3.3 times more enzyme activity was found in the neonicotinoid-resistant A. gossypii populations in the province of Adana in 2016 (Ulusoy et al 2018). These results provide evidence that these populations have metabolic resistance still in this region.…”
Section: Resultssupporting
confidence: 67%
“…5.9 times more AChE activity was observed in comparison to the reference population (Table 1). In parallel with these results, another study that was carried out in this region found 6.5 times more AChE activity in comparison to the reference population for A. gossypii populations (Ulusoy et al 2018, Velioglu et al 2008. As in the cases of AChE enzyme activity levels, the highest GST enzyme activities were found in the Çiftlikler population (2.68 U/ml) and Hamitbey population (2.33 U/ml).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations